PENANGANAN BAGGAGE IRREGULARITIES PADA EVENT MOTO-GP 2023 OLEH PETUGAS LOST AND FOUND PT GAPURA ANGKASA DI BANDAR UDARA INTERNASIONAL ZAINUDDIN ABDUL MADJID LOMBOK - Asma Wulandari; Rezty Fauziah Novianti (ADISAM PUBLISHER, 2024)
The lost and found unit is a work unit whose task is to check passengers' luggage by matching the baggage code on each passenger's baggage tag, as well as handling excess, lost and damaged luggage encountered by passengers. This research aims to determine the handling of baggage irregularities at the 2023 Moto-GP event in handling problematic baggage cases by lost and found officers at PT. Angkasa Gate at Zainuddin Abdul Madjid International Airport, Lombok. This research was conducted in 2023 at Zainuddin Abdul Madjid Lombok International Airport using qualitative methods and data collection was sourced from passengers who experienced baggage problems when arriving at Zainuddin Abdul Madjid Lombok International Airport. The next source comes from extracting data sources through online interviews with lost and found units regarding passengers' baggage irregularity handlers, direct observations of objects, documents such as PIR (Property Irregularity Report) and related operational procedures. The results of the research show that the procedures for handling baggage irregularities that have been carried out by the lost and found unit are carrying out inspections and recording if there is damage or other problems with passenger baggage in a document called PIR (Property Irregularity Report) which will later be published. Fill in the passenger's identity and then sign it. If there is a problem with the passenger's baggage, the passenger has the right to apply for compensation. The obstacles faced by lost and found units during the 2023 Moto-GP event itself are very diverse, one of which is communication